KEMUNCULAN OEDIPUS COMPLEX DAN KONSEKUENSINYA DALAM NOVEL SONS AND LOVERS D.H. LAWRENCE - MONALISA, MONICA (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2017)
ABSTRACT This research entitles: â€œKemunculan Oedipus Complex dan Konsekuensinya dalam novel Sons and Lovers karya D. H. Lawrenceâ€. This analysis is mainly aimed at finding out the emergences and the consequences of the Oedipus Complex shown by the characters in this novel. This research is conducted in order to answer the two questions: how the emergence appear in the novel and what consequences of Oedipus Complex are. The theory used for this analysis is psychological theory by Sigmund Freud (in Suryabrata, 2012). His theory is about the psychological analysis which is used to analyze the data. There are some steps done in collecting the data after mastering the theory and novel. The collected data is from library and internet research. When the data were collected and identified, the data were rewritten and they were classified according to their types. The results show that there are some aspects that influence the emergence of Oedipus Complex behavior. They are, relationship between mother and son, jealously against brother, violent behavior from a father, and a disharmony family. And the consequences that appear from Oedipus Complex behavior are guilty feeling and self punishment. Keywords: Oedipus Complex, psychology analysis, emergence, consequences